1976
DOI: 10.1113/jphysiol.1976.sp011452
|View full text |Cite
|
Sign up to set email alerts
|

The number of sodium ion pumping sites in skeletal muscle and its modification by insulin.

Abstract: 4. Insulin stimulated the Na pump in muscles whose pumping sites had been inhibited by ouabain and then transferred to a glycoside-free solution. This stimulation was observed before detecting any recovery of the initial pumping activity.5. When both the resting and the insulin-stimulated 22Na efflux had been blocked by ouabain, an additional dose of insulin, in a duabain-free solution, had no further effects on 22Na efflux.6. The effects of insulin were unaffected by cycloheximide or by high concentrations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
3

Year Published

1976
1976
1994
1994

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 32 publications
4
44
3
Order By: Relevance
“…Although this change is difficult to interpret, insulin appears to play an important role in sodiumpotassium transport in a number of tissues. Insulin receptor density in monocytes increases as a result of training (39); Although the specific effect of endurance training on insulin receptors has not been studied in muscle, studies on skeletal muscle of various species have shown that independently of glucose, insulin hyperpolarizes cells (40), stimulates K uptake (41), increases Na,K-ATPase activity (42), augments [3H]-ouabain binding (43), enhances affinity of pump sites on the inner membrane surface to sodium ions (44,45), and may multiply pump sites (46). Most recently, evidence has been cited that insulin facilitates Na'-proton exchange (47), allowing Na' to stimulate the pump, which generates electronegativity.…”
Section: Discussionmentioning
confidence: 99%
“…Although this change is difficult to interpret, insulin appears to play an important role in sodiumpotassium transport in a number of tissues. Insulin receptor density in monocytes increases as a result of training (39); Although the specific effect of endurance training on insulin receptors has not been studied in muscle, studies on skeletal muscle of various species have shown that independently of glucose, insulin hyperpolarizes cells (40), stimulates K uptake (41), increases Na,K-ATPase activity (42), augments [3H]-ouabain binding (43), enhances affinity of pump sites on the inner membrane surface to sodium ions (44,45), and may multiply pump sites (46). Most recently, evidence has been cited that insulin facilitates Na'-proton exchange (47), allowing Na' to stimulate the pump, which generates electronegativity.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of active Na-K transport may either be the result of increased rate of pumping in existing Na pumps (Joiner & Lauf, 1975), de novo synthesis of pumps (Jorgensen, 1972), or unmasking of latent pumps (Erlij & Grinstein, 1976). In order to identify the mechanism of action of a given stimulus, it is important to distinguish between these possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of transport of glucose in fat and muscle cells are the best documented cases of recruitment of transporters (Wardzala, Cushman & Salans, 1978;Suzuki & Kono, 1980;Cushman & Wardzala, 1980;Ramlal, Sarabia, Bilan & Klip, 1988). Insulin also increases the number of ouabain binding sites in the surface membrane of skeletal muscle (Erlij & Grinstein, 1976). Recent evidence indicates that this effect is due to delivery of Na+-K+-ATPase from cytoplasmic pools into the surface membrane (Omatsu-Kanbe & Kitasato, 1990;Hundal, Marette, Mitsumoto, Ramlal, Blostein & Klip, 1992).…”
mentioning
confidence: 99%